Socialnomics how social media transforms the way we live and do business - Qualman, Erik 1972- (Wiley, 2011)
Welcome to the world of socialnomics, where consumers and the societies they create online have profound effects on our economy and the businesses that operate within it. Online word of mouth, social search, social commerce, and the influence of peer groups are making traditional marketing strategies obsolete. As a result, we no longer have a choice on whether we do social media; the question is how well we do it.